A bilinear robust state estimation method for electric thermal integrated energy system. (June 2020) - Yang, Xiaonan; Sun, Bo; Han, Feng; Lang, Yansheng
Abstract: A bilinear robust state estimation method for electric thermal integrated energy system (IEHS) is proposed. First, the linear weighted least absolute value (WLAV) model of IEHS is constructed by introducing auxiliary variables, and then the state variables are estimated by solving a quadratic programming model with a nonlinear transformation. The advantage of the proposed method is that it has a high calculation efficiency. The effectiveness of the proposed method is verified on the IEHS test system.